Code of conduct as a source of international legal regulation for transnational corporations - Kurnicki, Leszek (European Journal of Social Science Education and Research, 2025)
This article discusses the possibility of adopting and using a code of conduct for transnational corporations as an international legal regulator of their activities. Author analyses the attempts of intergovernmental organizations (in particular the UN) aimed at adopting such a comprehensive act, as well as the reasons why they turned out to be untenable. Simultaneously, author assesses the effectiveness of existing international legal measures which focus the activities of transnational corporations.
Keywords: transnational corporations, code of conduct, corporative law, international law, globalisation, the United Nations.